Delayed Gastric Emptying after Pancreatic Surgery: Analysis of Factors Determinant for the Short-term Outcome - Noorani, A.; Rangelova, Elena; Del Chiaro, M.; Lundell, Lars Ragnar; Ansorge, Christoph (Frontiers in Surgery, 2016)
Background: Delayed gastric emptying (DGE) frequently complicates pancreatoduodenectomy (PD). Mainly DGE develops as consequence of postoperative intra-abdominal complications (secondary), whilst the incidence of primary DGE (i.e. not related to surgical complications) has rarely been studied. Moreover the pathogenesis of DGE is complex and needs to be further elucidated. The present study aimed at highlighting potential mechanisms behind primary and above all secondary DGE by studying a variety of different pancreatic surgical procedures. Patients and methods: During the time period 2008 – 2011, 327 patients underwent pancreatic resective procedures at Karolinska University Hospital. Of these 242 were PD and 56 tail resections, 17 had a duodenal preserving pancreatectomy for chronic pancreatitis and 15 patients with familial duodenal polyposis had a pancreas preserving duodenectomy. All postoperative courses were assessed and scored according to Clavien-Dindo. The presence of DGE was evaluated and recorded according to the definition launched by the International Study Group for Pancreatic Surgery (ISGPS). Crude associations were studied in a univariate model, followed by a multivariate analysis of the respective factors. The associations were presented as odds ratios (ORs) with 95% confidence intervals (CIs). Results: In total DGE emerged during the postoperative course in about 40 % of the PD cases. About half of those (n= 47) were scored as being primary. The majority of the primary DGEs were classified as A (n= 26) and only 4 as grade C, whereas among the secondary cases significantly more patients were scored as grade C (p< 0, 01). In those submitted to a pancreatic body and tail resection 25 % reported DGE. The distribution of the different grades of DGE in patients with a tail resection followed the same pattern with a predominance of Grade A cases with an equal distribution between those being scored as primary and secondary. Duodenal preservation as well as keeping the pancreas intact following duodenectomy was not followed by primary DGE. Multivariate risk factor analyses for the development of primary GE revealed no specific risk profile except for high age. Conclusion: DGE is frequently seen after different surgical procedures directed towards the pancreatic gland. DGE is most